Are Cement Sector Companies Listed on Indonesia Stock Exchange (IDX) Compliant in Sustainability Reports Disclosure? English - Sinta Fatmaria Tantri; Kurnia Ekasari; Hesti Wahyuni (Journal of Applied Business, Taxation and Economics Research, 2023)
This study aims to analyze the level of compliance in the disclosure of sustainability reports to cement sector companies listed on the Indonesia Stock Exchange (IDX) use Intiative Global reporting (GRI).  The objects of this study are PT Semen Baturaja (Persero) Tbk, and PT Semen Indonesia (Persero) Tbk.  The research method used is qualitative with secondary data, namely the sustainability report in 2021.  The data collection technique in this study is documentation through the company's website. Data analysis techniques using data collection, data recording, and data analysis and interpretation. The results of this study show that PT Semen Baturaja (Persero) Tbk has a partially applied compliance rate in the disclosure of GRI general standards of 48.75. Meanwhile, PT Semen Indonesia (Persero) Tbk has a Partially Applied compliance rate with a higher percentage of 59.37%. The limitation of this study uses secondary data, therefore future studies can use primary data and expand the range of standards used in research.  Previous research on sustainability compliance is still small, therefore this study can be a reference for future research by developing the limitation.